A New Image Encryption Scheme Based on Dynamic S-Boxes and Chaotic Maps - Rehman, Atique Ur; Khan, Jan Sher; Ahmad, Jawad; Hwang, Soeng Oun (3D research, 2016)
Substitution box is a unique and nonlinear core component of block ciphers. A better designing technique of substitution box can boost up the quality of ciphertexts. In this paper, a new encryption method based on dynamic substitution boxes is proposed via using two chaotic maps. To break the correlation in an original image, pixels values of the original plaintext image are permuted row- and column-wise through random sequences. The aforementioned random sequences are generated by 2-D Burgers chaotic map. For the generation of dynamic substitution boxes, Logistic chaotic map is employed. In the process of diffusion, the permuted image is divided into blocks and each block is substituted via different dynamic substitution boxes. In contrast to conventional encryption schemes, the proposed scheme does not undergo the fixed block cipher and hence the security level can be enhanced. Extensive security analysis including histogram test is applied on the proposed image encryption technique. All experimental results reveal that the proposed scheme has a high level of security and robustness for transmission of digital images on insecure communication channels.